(untitled) (Nordic Journal of African Studies, 2001)
This article argues that globalisation, which has become an undisputed phenomenon in the post-Cold War era, is not new. Rather, it is an acceleration of the process of capital accumulation and exportation to the South, which has been in place since the seventeenth century. However, in the post-Cold War era this process changed qualitatively from its previous character with the emergence of new global institutions such as the World Trade Organisation (WTO) and regimes like the Uruguay Rounds Agreements (URA) which supervise and regulate trade among nations. The contemporary globalisation has spawned competition, which has ultimately worked to the disadvantage of Africa. Consequently, while other regions find niches in the increasingly competitive global market and thus getting integrated into the international economy, Africa’s posture in the global economy is getting increasingly ambivalent. On the one hand, Africa’s increasing marginalisation is reflected in its declining share of world trade, overseas development assistance (ODA), direct foreign investments (DFI), and the loss of its previous comparative advantage in the supply of raw materials. On the other hand, Africa’s dependence on the global market and International Financial Institutions (IFIs) is growing. This uncertain position in the global economy has also produced adverse consequences such that while Africa’s economies stagnate or decline under the weight of market liberalisation, the economies of East Asia, for example, grow. In general, globalisation created major challenges for Africa. These challenges include the erosion of the continent’s tenuous sovereignty, which has been subverted by market forces and IFIs; the creation of salutary conditions for intra-state contestations and armed conflicts; impeding Africa’s efforts at establishing a common market; and hastening environmental degradation on the continent. It is argued further that the very logic of globalisation vitiates the efforts of African states to adequately respond to these challenges.